2019
DOI: 10.1098/rsif.2019.0202
|View full text |Cite
|
Sign up to set email alerts
|

Invariant predictions of epidemic patterns from radically different forms of seasonal forcing

Abstract: Seasonal variation in environmental variables, and in rates of contact among individuals, are fundamental drivers of infectious disease dynamics. Unlike most periodically-forced physical systems, for which the precise pattern of forcing is typically known, underlying patterns of seasonal variation in transmission rates can be estimated approximately at best, and only the period of forcing is accurately known. Yet solutions of epidemic models depend strongly on the forcing function, so dynamical predictions-suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…It has also been demonstrated that for certain values of system parameters the nonautonomous models of recurrent epidemics (measles, mumps, rubella, H5N1 avian influenza) show chaotic behavior 6,[19][20][21] . Traditional SIR-like epidemic models are dissipative nonlinear low-dimensional systems with constant, periodic, quasiperiodic 22 , or term-time 3,23 external forcing whose dynamics a) Electronic mail: tkovacs@general.elte.hu is governed by (chaotic) attractors in phase space. Furthermore, even if the long-term dynamics is regular and the final state of the system is a fixed-point attractor the route to this condition might be rather complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that for certain values of system parameters the nonautonomous models of recurrent epidemics (measles, mumps, rubella, H5N1 avian influenza) show chaotic behavior 6,[19][20][21] . Traditional SIR-like epidemic models are dissipative nonlinear low-dimensional systems with constant, periodic, quasiperiodic 22 , or term-time 3,23 external forcing whose dynamics a) Electronic mail: tkovacs@general.elte.hu is governed by (chaotic) attractors in phase space. Furthermore, even if the long-term dynamics is regular and the final state of the system is a fixed-point attractor the route to this condition might be rather complex.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even if the long-term dynamics is regular and the final state of the system is a fixed-point attractor the route to this condition might be rather complex. Many studies examined the role of finite-time irregularity in ecological models [24][25][26][27] as well as in epidemic dynamics 9,23,28,29 concluding the relevance of transient behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, how 493 interventions influence the frequency structure and seasonality of epidemic time series 494 over decades and centuries is much more subtle [56, 74,75]. While preliminary work has 495 been promising [76], careful estimation [77,78] and analysis [75,79]…”
mentioning
confidence: 99%
“…Moreover, the time series is so long that the underlying pattern of seasonal forcing probably changed substantially. Changes in seasonal forcing can be accommodated in predictions [16,106], and estimation of underlying seasonal variation in transmission is becoming easier [107]; however, obtaining a convincing mechanistic explanation for all the structure we have identified in London's smallpox dynamics represents a major challenge.…”
Section: Explaining Transitions In Smallpox Dynamicsmentioning
confidence: 99%
“…Ultimately, we anticipate that meeting this challenge will involve further developments of the existing theory of transitions in epidemic patterns [13][14][15][16]106], coupled with state-of-theart methods of inference to obtain parameter estimates for dynamical models [108][109][110][111][112].…”
Section: Explaining Transitions In Smallpox Dynamicsmentioning
confidence: 99%